Evaluación de la dinámica temporal de la cobertura vegetal del Cantón Salcedo mediante el uso de imágenes satelitales desde el año 2000 al 2020 - Changalombo Valencia, Diego Armando (2021)
Research related to the progressive changes in vegetation coverage and land use is becoming increasingly important in environmental research as it allows to evaluate over time the loss or gain of vegetation coverage. Moreover, in recent decades, anthropogenic activities have become the main problem in the transformation of ecosystems, modifying or destroying them in order to develop their activities. The main objective of this research was to evaluate the temporal dynamics of the vegetation coverage of the Salcedo Canton from 2000 to 2020, the study was conducted based on multispectral satellite images Landsat 7 ETM+, 8 OLI and sentinel 2, the methodology applied for the vegetation coverage classification is supervised, using the maximum likelihood algorithm and the application of NDVI in the QGIS program, also the classification was validated by training areas and verifications taken in the field, which identified seven coverages: forest, bare soils, moorland, agricultural mosaic, urban areas, rivers or lakes, shrubs and bushes, in this way the changes in vegetation coverage were evaluated, as well as a transition matrix where the changes that occurred every two periods were analyzed in order to identify and quantify the changes that occurred within the study area. Therefore, the results indicate that from 2001 to 2020 the Salcedo Canton has suffered progressive changes in vegetation coverage, one of the most significant changes is the loss of moorland and the increase of agricultural mosaics, with the moorland decreasing by 5812.84 hectares by 2020 and the agricultural mosaic increasing by 12216.43 hectares more than in 2001. The data captured by all these sensors were stored in the form of tables and maps, from which information was generated to help update the land use plan for the Salcedo Canton with respect to current land use and thus be able to plan the territory for the conservation of natural resources.